METHODOLOGY OF TEACHING THE GRAPHIC EDITOR ADOBE PHOTOSHOP IN THE PROFILE COURSE IN COMPUTER SCIENCE (Conference Zone, 2022)
The relevance of this study is determined by the need to resolve the contradiction between the requirements of society for the training of school graduates in the field of information technology related to graphics and the lack of a developed methodology for specialized training in these technologies